The reality of the administrative values of sports activities in the faculties of the University of Baghdad from the point of view of leaders and those related to the divisions and units of student activities - aljabar, Zaid; Mohammed, Zaydoon (Journal of Physical Education, 2023)
The research aimed to identify the level of reality of the administrative values of sports activities in the faculties of the University of Baghdad from the point of view of administrative leaders related to the divisions and units of student activities, and the case study method was adopted from the descriptive approach, on a randomly selected sample of (251) individuals representing (53.291%) of the original community represented by the administrative leaders related to the work of sports activities in the formations of the University of Baghdad who continue their official working hours for the academic year (2022/2023), and they are both the president and members of the College Council, And the rapporteurs of the branches / departments, and the officials of the quality assurance and continuing education divisions, whose total number is (471) individuals, and they are distributed by nature among (24) colleges of these administrative formations, It is on the basis that they are the community of the phenomenon surveyed in the research problem themselves, and the survey sample was randomly selected by (10) individuals by (2.123%) of the research community, and the scale of administrative values of sports activities was adopted, and experimented exploratory and then conducted the survey and processed the results with the (SPSS) system to be the conclusions and applications that the divisions and units of student activities have an acceptable level of administrative values for sports activities from the point of view of administrative leaders in the formations of the University of Baghdad, and the point of view of administrative leaders in the formations of the University of Baghdad achieved a level Raising the level of administrative values of sports activities needs attention to supporting the values of competition and investing opportunities in the divisions and units of student activities from the point of view of administrative leaders in the formations of the University of Baghdad, and it is necessary to work to enable workers in the divisions and units of student activities to raise the level of competition values and invest opportunities that increase the level of administrative values of sports activities.